The Impact of Parental Involvement, Parent-Teacher Communication, and Study Environment on the Academic Success of Bachelor Students: A Case Study of Bachelor Level Students. - Phuyal, Pradeep (Medha: A Multidisciplinary Journal, 2023)
Purpose: This study aims to investigate the relationship between parental involvement and academic achievement among bachelor-level students, focusing on specific forms of parental engagement and influencing factors.Methodology: A sample of 225 students from various colleges in Koshi Province was analyzed using Pearson correlation tests and regression analysis. Data were collected through Google Forms, examining how parental involvement correlates with academic success across different demographics.Findings: The study reveals a positive correlation between increased parental involvement and academic achievement (r = 0.544, p = 0.000). Effective parent-teacher communication (r = 0.676, p = 0.001) and a supportive study environment (r = 0.695, p = 0.000) are significant factors influencing academic success. The regression model, incorporating these factors, accounts for a substantial portion of the variance in student achievement (R² = 0.4872, F(3, 221) = 2.809, p = 0.040). The model demonstrates no issues of multi-collinearity (VIF values between 1.211 and 2.142), no heteroscedasticity (student deleted residuals between -2.331 and 2.550, Cook’s Distance maximum at 0.053), and no outliers or excessive leverage (centered leverage values between .001 and .105).Implications: Enhancing parental involvement, fostering positive study environments, and improving parent-teacher communication are crucial for supporting academic success in bachelor-level students.Value: This study enhances understanding of academic achievement's multifaceted nature and underscores the need for collaboration between parents and educational institutions to boost students' academic performance.